Pendampingan Guru-Guru SMPN 49 dan 53 Kota Makassar Dalam Pengembangan Perangkat Pembelajaran Abad 21 Untuk Meningkatkan Kompotensi Guru - Munirah Munirah; Nurlina Subair (Lembaga Layanan Pendidikan Tinggi Wilayah IX Sulawesi, 2019)
This service aims to solve partner problems (teachers of 49 and 53 Junior High School Makassar City), namely developing 21st century learning tools to increase teacher pedagogical potential. The form of this service is training with direct assistance. Output targets in training activities are (1) Increasing teacher knowledge in developing 21st century-based learning tools, namely learning implementation plans (lesson plans), worksheets, and assessment instruments; (2) Increase teacher knowledge in developing teacher competency. Output targets in mentoring activities are to produce products in the form of learning tools based on 21st century learning including Product Learning Implementation Plan (RPP), Student Worksheet Products, and Product Assessment Instruments. The dedication method used to achieve the goal (output) is by adopting a mechanism for implementing action research which consists of 4 (four) stages, namely: planning, action, observation-evaluation, and reflection. The planning stage is the preparation stage, the action stage is the core stage (the realization of the IbM in the form of training and mentoring, the observation and evaluation stage is the stage of measuring the success of the program, while the reflection stage is the policy making stage (strategic step) in continuing the program to improve things that have been done before The results of the teacher training assistance at 49 and 53 Junior High School Makassar City are categorized as successful and very active in developing 21st century based learning tools.